(untitled) (Journal of Oriental Studies, 2016)
Translation of phraseological units, especially figural, becoming very difficult. This may be because lots of them are pictorial, emotional, belong to the special parlance and have clear-cut national character. During the translation of the fixed collocations, it is important to consider contextual cue they used in. Many phraseological units in English are polysemous and stylistically various and it is making them hard to translate. In “Translation of phraseological units used in Abay’s works to Chinese language” author analyzing translations of phraseological units in Chinese versions of the works of great writer made by famous Chinese translator and scientist Ha Huanzhang.